STUDI PENCIPTAAN KARYA SITE SPECIFIC DANCE “HELAI KERTAS” - Supendi, Eko; Isnanta, Satriana Didiek (Acintya, 2020)
ABSTRACTDance has experienced extraordinary development. Now, dance is no longer in the area of fairies but has entered the modern civilization, the tradition is shifted to the industry and academic. This is because of the role of academic dancers who conduct the research, both creation studies and scientific studies. Dance has become the object of laboratories in the studios of art academics in Indonesia and various parts of the world, so that dance laboratories and studios have emerged in various places in Indonesia. Now dance is not only seen as practicing soul, dance is no longer limited to the beauty of aesthetic invisible , but dance  also has explored other art worlds, such as theater and fine arts.Now it is difficult to distinguish between dance and theater performance. The above phenomenon often becomes a trend of artists. Art observers call it a contemporary phenomenon. Contemporary phenomena continue to develop in artists and academic world. Contemporary art is critical towards social problems around it as well as the art itself. Contemporary spirit does not only break the ice of one art discipline but also across art disciplines. Almost all elements of dance are explored and developed, one of which is site specific dance. A genre of contemporary dance that focuses on creating dance works using special places.This study uses an artistic research method. The researchers as well as the creators of site specific dance works is in the lobby of the H.U office Solopos. The research stages are in accordance with the stages of artistic research.Keywords: site specific dance, space, body, time, dance.  ABSTRAK Seni tari telah mengalami perkembangan yang luar biasa.  Sekarang, tari tidak lagi berada di wilayah peri-peri, tetapi telah masuk ke sentrum peradaban modern, dari kantong-kantong tradisi bergeser ke kantong-kantong industri dan akademik. Hal tersebut tidak lepas dari peran penari akademik yang melakukan riset, baik studi penciptaan maupun kajian ilmiah. Tari telah menjadi objek laboratorium di studio-studio akademisi seni di Indonesia dan berbagai belahan dunia, sehingga bermunculan laboratorium-laboratorium dan studio tari di berbagai tempat di Indonesia.Tari saat ini dipandang tidak saja berolah sukma, tari tidak lagi sebatas keindahan estetika yang kasat mata, tetapi tari sudah menjelajah dunia seni lainnya, seperti teater dan seni rupa.Sekarang sulit membedakan antara penyajian tari dan teater. Fenomena di atas sering menjadi trend para seniman individual. Kalangan pengamat seni menyebut fenomena tersebut sebagai fenomena kontemporer. Fenomena kontemporer terus berkembang dalam kalangan seniman dan lingkungan akademik. Seni kontemporer selain kritis terhadap persoalan sosial yang ada di sekitarnya juga kritis kepada seninya sendiri. Spirit kontemporer tidak hanya mendobrak kebekuan sekat –sekat satu disiplin seni, tetapi juga lintas disiplin seni. Hampir semua elemen tari dieksplorasi dan dikembangkan, salah satunya adalah site specific dance. Sebuah genre seni tari kontemporer yang fokus kepada penciptaan karya tari menggunakan tempat-tempat yang khusus.Penelitian ini menggunakan metode penelitian artistik, dimana peneliti sekaligus pencipta karya site specific dance di lobi kantor H.U. Solopos yang tahapan penelitiannya sesuai dengan tahapan riset artistik. Kata kunci: site specific dance, ruang, ketubuhan, waktu, tari.